Der Mensch als Bild des unergründlichen Gottes Von der Theologie zur Anthropologie und zurück - Huian, Georgiana; Wyss, Beatrice; Hirsch-Luipold, Rainer (De Gruyter, 2023)
God is unfathomable and unknowable. This thought is deeply entrenched in the Jewish-Christian tradition. On the other hand, Biblical texts speak of the human being or Christ as having been created in God's image. How can these two things be conceived of together? These articles build bridges between East and West, between history and the present, bringing ancient and medieval writings into dialogue with contemporary theological positions.